Characteristics And Acceptability Of Crispy Noodles Made With Corn (Zea Mays L.) And Inulin Flour Substitutes - Nida Faizah Khoirunnisa khoirunnisa; Annis Catur Adi (CV. AFDIFAL MAJU BERKAH, 2026)
Obesity is a growing nutritional problem, including in Indonesia. The habit of consuming high-calorie, low-fiber foods such as noodles contributes to the risk of obesity. Corn silk, often considered waste, is rich in fiber, flavonoids, saponins, tannins, beta-carotene, and other vitamins that are beneficial to health. Corn silk is produced in abundance; specifically, for every 5 tons of corn, 3.5% consists of corn silk. The potential for utilizing this byproduct can be combined with inulin flour, which is high in fiber content and has prebiotic properties. This study aims to determine the effect of substituting corn silk flour and inulin flour on the acceptability of crispy noodle products. The research design used was a pure experimental design with a completely randomized design (CRD), consisting of 3 formulations: one control formulation (F0) and two modified formulations (F1, F2). The panelists were 30 adults aged 18 years and older. The acceptability test results showed that the modified formula most preferred by the panelists was F1. There were significant differences in color, taste, texture, and aftertaste characteristics (p ≤ 0.05). Thus, the substitution of corn silk flour and inulin flour in crispy noodle products is still sensorially acceptable, with F1 as the best modified treatment formula.